Accuracy comparison of MR elastography and biological markers in detecting liver fibrosis and predicting postoperative ascites. Issue 9 (September 2021) - Sato, Naoya; Kenjo, Akira; Nishimagi, Atsushi; Kimura, Takashi; Okada, Ryo; Ishigame, Teruhide; Kofunato, Yasuhide; Yamada, Shoki; Hashimoto, Yuko; Marubashi, Shigeru
Abstract: Background: This retrospective study aimed to compare the discriminative performance between magnetic resonance elastography (MRE) and biological markers in detecting liver fibrosis and in predicting postoperative ascites (PA). Methods: We enrolled 77 patients consecutively who underwent hepatectomy between March 2017 and June 2019. Liver fibrosis was histopathologically graded using the METAVIR scoring system as reference. Discriminative performance of non-invasive assessments in detecting different stages of liver fibrosis and predicting PA was evaluated by receiver–operator curve analysis. Results: The concordance indices (C-indices) for MRE and biological markers for detecting significant fibrosis (≥F2) and cirrhosis (F4) were: MRE, 0.84 and 0.86; Wisteria floribunda agglutinin + Mac-2 binding protein (WM2BP), 0.63 and 0.71; Hyaluronic acid (HA), 0.72 and 0.75; 7 S-type 4 collagen (T4C), 0.61 and 0.66; APRI, 0.76 and 0.83; and Fib-4, 0.75 and 0.76. Univariable logistic analysis for predicting PA showed that C-indices were 0.751 (p = 0.007), 0.798 (p = 0.106), 0.771 (p = 0.050), 0.674 (p = 0.855), 0.655 (p = 0.263), and 0.560 (p = 0.640) for MRE, WM2BP, Fib-4, HA, APRI, and T4C, respectively. Conclusion: MRE has a higher diagnostic performance than biological markers in detecting the stages of liver fibrosis and is a predictor for PA after hepatectomy.